2008
DOI: 10.1093/molbev/msn243
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism and Mutualism in Wolbachia: What the Phylogenomic Trees Can and Cannot Say

Abstract: Ecological and evolutionary theories predict that parasitism and mutualism are not fixed endpoints of the symbiotic spectrum. Rather, parasitism and mutualism may be host or environment dependent, induced by the same genetic machinery, and shifted due to selection. These models presume the existence of genetic or environmental variation that can spur incipient changes in symbiotic lifestyle. However, for obligate intracellular bacteria whose genomes are highly reduced, studies specify that discrete symbiotic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 60 publications
1
95
0
6
Order By: Relevance
“…In our unrooted MLST tree, supergroup E is sister to the A + H clade; however, the sister‐group relationship between A and H is not well supported (Figure 1). As supergroup H was considered the sister‐group of supergroup E in most of the previous studies (Bordenstein et al., 2009; Lefoulon et al., 2016; Lo et al., 2007), the relationship between A, H, and E would be better illustrated when more MLST sequences are available, especially for supergroup H. The phylogenetic inferences based on 16S rRNA and ftsZ genes indicate that supergroups K and L might also be close to supergroup E (Fig. S7A).…”
Section: Discussionmentioning
confidence: 99%
“…In our unrooted MLST tree, supergroup E is sister to the A + H clade; however, the sister‐group relationship between A and H is not well supported (Figure 1). As supergroup H was considered the sister‐group of supergroup E in most of the previous studies (Bordenstein et al., 2009; Lefoulon et al., 2016; Lo et al., 2007), the relationship between A, H, and E would be better illustrated when more MLST sequences are available, especially for supergroup H. The phylogenetic inferences based on 16S rRNA and ftsZ genes indicate that supergroups K and L might also be close to supergroup E (Fig. S7A).…”
Section: Discussionmentioning
confidence: 99%
“…(Dumler et al, 2001;Dunning Hotopp et al, 2006b). Numerous phylogenetic analyses of Wolbachia have been undertaken, including single-locus and multi-locus approaches (Bordenstein et al, 2008;Casiraghi et al, 2005;Lo et al, 2002;O'Neill et al, 1992;Werren et al, 1995;Zhou et al, 1998). Despite maternal inheritance in arthropods, the phylogenetic distribution of these Wolbachia is not concordant with that of their hosts (Baldo et al, 2006b;O'Neill et al, 1992;Werren et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, current phylogenetic and recombination analysis supports all Wolbachia strains being formally included in the single species Wolbachia pipientis (Lo et al, 2007). To help distinguish isolates, Wolbachia strains have been divided into eight phylogenetic clades termed supergroups (Bordenstein et al, 2008;Lo et al, 2007). The A and B supergroup Wolbachia are the most common and are widespread in arthropods as single or double infections (Werren et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of sequence information obtained with targeted bacterial genes includes16S rDNA (partial small subunit ribosomal DNA, groEl (heat shock protein gene), wsp (outer surface coat protein gene) (Baldo et al, 2006;Paraskevopoulos et al, 2006) and ftsZ (cell division gene), Wolbachia infections have been characterized and divided into eight super groups A-H (Zhou et al,1998;Bordenstein et al, 2009;Ros et al, 2009) Moreover, some recent literature reported that infectious strains of Wolbachia can further be classified into 3 more super groups, that's A-K super orders (Zhou et al,1998;Bordenstein et al, 2009;Ros et al, 2009;Salunke et al, 2010) as shown in Figure b (1): Table. 1. …”
Section: Phylogeny and Classification Of Wolbachiamentioning
confidence: 99%